Implementing Ethical Recruitment of Migrant Workers: Evidence from the Palm Oil Sector in Malaysia - Andika Wahab (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
Growing allegation of irregularities in the conduct of migrant workers’ recruitment drives global effort to eliminate unethical practices in the migration industry. As part of the international value chain, palm oil companies in Malaysia are expected to implement ethical recruitment practices. This study is an attempt to assess the employers’ commitment and practices in implementing ethical recruitment in Malaysia. Deriving from four palm oil mills (employers) and further validated through a survey conducted against 92 Nepalese workers – this study argues that while employers have committed to cover certain costs of their migrant workers’ recruitment, they lack a clear policy commitment, due diligence and monitoring against the labour recruiters. Consequently, the labour recruiters (including the intermediaries) mainly in Nepal have imposed another set of recruitment costs which already covered by the employers in Malaysia. Alarmingly, the Nepalese workers have paid even a higher cost of recruitment than the cost borne by the employers. For ethical recruitment to be effectively implemented, the employers’ monetary commitment to cover the cost of their workers’ recruitment must be complemented with efforts to engage and monitor the conduct of the labour recruiters in migrant workers’ origin country.